Metabolism of Odorant Molecules in Human Nasal/Oral Cavity Affects the Odorant Perception. (29th June 2019) - Ijichi, Chiori; Wakabayashi, Hidehiko; Sugiyama, Shingo; Ihara, Yusuke; Nogi, Yasuko; Nagashima, Ayumi; Ihara, Sayoko; Niimura, Yoshihito; Shimizu, Yuya; Kondo, Kenji; Touhara, Kazushige
Abstract: In this study, we examined the mode of metabolism of food odorant molecules in the human nasal/oral cavity in vitro and in vivo. We selected 4 odorants, 2-furfurylthiol (2-FT), hexanal, benzyl acetate, and methyl raspberry ketone, which are potentially important for designing food flavors. In vitro metabolic assays of odorants with saliva/nasal mucus analyzed by gas chromatography mass spectrometry revealed that human saliva and nasal mucus exhibit the following 3 enzymatic activities: (i) methylation of 2-FT into furfuryl methylsulfide (FMS); (ii) reduction of hexanal into hexanol; and (iii) hydrolysis of benzyl acetate into benzyl alcohol. However, (iv) demethylation of methyl raspberry ketone was not observed. Real-time in vivo analysis using proton transfer reaction-mass spectrometry demonstrated that the application of 2-FT and hexanal through 3 different pathways via the nostril or through the mouth generated the metabolites FMS and hexanol within a few seconds. The concentration of FMS and hexanol in the exhaled air was above the perception threshold. A cross-adaptation study based on the activation pattern of human odorant receptors suggested that this metabolism affects odor perception. These results suggest that some odorants in food are metabolized in the human nasal mucus/saliva, and the resulting metabolites are perceived as part of the odor quality of the substrates. Our results help improve the understanding of the mechanism of food odor perception and may enable improved design and development of foods in relation to odor.